Sprachbildender Vorstellungsaufbau für verschiedene mathematische Konzepte: Brüche in Klasse 6 - Wessel, Lena; Kuzu, T.; Prediger, Susanne (Sprachbildender Mathematikunterricht in der Sekundarstufe - ein forschungsbasiertes Praxisbuch)

Fach- und sprachintegrierte Ansätze für Neuzugewanderte - Sprütten, F.; Wessel, Lena; Zentgraf, K.; Prediger, S. (Sprachbildender Mathematikunterricht in der Sekundarstufe. Ein forschungsbasiertes Praxisbuch)

Language for Mathematics in Vocational Contexts. Handbook for teachers and facilitators - Wessel, Lena; Prediger, S.; Stein, A.; Wijers, M.; Jonker, V.

University Mathematics Didactic Research on Number Theory, Algebra, Discrete Mathematics, Logic - Biehler, Rolf; Durand-Guerrier, Viviane (Proceedings of the Third Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2020, 12-19 September 2020))
Keywords: Number Theory; Algebra; Discrete Mathematics; Logic; Research in University Mathematics Edcuation

Motivation of out-of-field teachers for participating in professional development courses in mathematics - Lünne, Steffen; Schnell, Susanne; Biehler, Rolf (European Journal of Teacher Education)
Keywords: Education

Theory-Based Design of Professional Development for Upper Secondary Teachers–Focusing on the Content-Specific Use of Digital Tools - Barzel, Bärbel; Biehler, Rolf (Professional development and knowledge of mathematics teachers)

Students’ Understanding of the Derivative Concept in the Context of Mathematics for Economics - Feudel, Frank; Biehler, Rolf (Journal für Mathematik-Didaktik)
Abstract The derivative concept plays a major role in economics. However, its use in economics is very heterogeneous, sometimes inconsistent, and contradicts students’ prior knowledge from school. This applies in particular to the common economic interpretation of the derivative as the amount of change while increasing the production by one unit. Hence, in calculus courses for economics students, learners should acquire an understanding of the derivative that is mathematically acceptable and connected to their prior knowledge, but which also takes into account its practical use in economics. In this paper we first develop a theoretical model describing such an understanding of the derivative for economics students. We then present an exploratory study investigating the extent to which economics students have such an understanding after their calculus course. The results indicate that many of them might not have acquired this kind of understanding, in particular concerning the common economic interpretation of the derivative. The study furthermore yields possible gaps in students’ understanding and possible misconceptions.
Keywords: Education; General Mathematics

Using Figurate Numbers in Elementary Number Theory – Discussing a ‘Useful’ Heuristic From the Perspectives of Semiotics and Cognitive Psychology - Kempen, Leander; Biehler, Rolf (Frontiers in Psychology)
Keywords: General Psychology

Was verstehen Schülerinnen und Schüler unter „Beweis“? – ausgewählte Ergebnisse einer Pilotstudie - Kempen, Leander; Krämer, Sandra; Biehler, Rolf (Beiträge zum Mathematikunterricht 2020)

Hochschuldidaktik Mathematik: Fachbezogenes Design und empirische Studien - Biehler, Rolf; Kempen, Leander; Paravicini, Walther (Beiträge zum Mathematikunterricht 2020)